2014
DOI: 10.1617/s11527-014-0496-z
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of strength prediction methods for alkali-activated fly ash

Abstract: The literature contains many proposed methods for proportioning alkali-activated binders for maximum compressive strength. Many of these methods have been developed using metakaolin, which is a relatively pure aluminosilicate powder. In recent years, fly ash has become a more common aluminosilicate source for alkali activation. However, fly ash is a more complex material than metakaolin, and activated fly ash may not follow the same trends as activated metakaolin. In this study, literature-recommended strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…However, Al can also act as a network modifier, with no need for charge compensation, even if cations are still present. The actual proportion between network forming and modifying Al could potentially be estimated by Raman spectroscopy, 27 Al NMR or 17 O NMR. But, it may be difficult to extract individual glasses from fly ash to be able to test them.…”
Section: The Influence Of Chemical Composition On Glass Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, Al can also act as a network modifier, with no need for charge compensation, even if cations are still present. The actual proportion between network forming and modifying Al could potentially be estimated by Raman spectroscopy, 27 Al NMR or 17 O NMR. But, it may be difficult to extract individual glasses from fly ash to be able to test them.…”
Section: The Influence Of Chemical Composition On Glass Reactivitymentioning
confidence: 99%
“…A study by Bumrongjaroen [26] has shown that the reactivity estimated from depth profiles of fly ash-type glasses leached in pH 12 LiOH largely corresponded to the NBO/T. Recently published results [27] on pastes prepared by alkali activation of siliceous fly ashes show a trend to higher compressive strength with increasing NBO/T of fly ash.…”
Section: The Influence Of Chemical Composition On Glass Reactivitymentioning
confidence: 99%
“…There have been recent attempts [14,15] to evaluate the effect of fly ash composition and properties (e.g., bulk composition, mineralogy, and particle size) on compressive strength of AAFA. However, there has not been a systematic effort to explicitly assess the effect of items (2)-(4) on the strength development.…”
Section: Research Objectivesmentioning
confidence: 99%
“…MSIA does not distinguish between glassy and crystalline phases, so the crystalline phases were included in the analysis. From the X-ray diffraction data, which were presented for each fly ash in Aughenbaugh et al (2014), crystalline phases present in these ashes include quartz, lime, and iron-bearing phases, such as maghemite, magnetite, or hematite. The compositions of the crystalline phases are not listed in the tables, as they correspond to those for crystalline quartz (SiO2), lime (CaO), or iron oxides, such as hematite, magnetite, or maghemite (Fe2O3 or Fe3O4).…”
Section: Resultsmentioning
confidence: 99%